Liquid Smoke of Red Fruit (Pandanus Conoideus. L.) Waste with Pyrolysis Method For Controlling Sweet Potatoes (Ipomea Batatas. L.) Pest - Fransisca Christiana DEWI; Sumiyati TUHUTERU; Andi ALADIN; Setiyawati YANI; Rohimah Handayani Sri LESTARI; Irwan Suluk PADANG; Bhaskara Anggarda Gathot SUBRATA (International Journal of Environmental, Sustainability, and Social Science, 2022)
Pandanus conoidus, or red fruit, is a nutrient-dense native Papuan plant, whereas Ipomea batatas are the main food for the Wamena people. Biomass from red fruit seed waste can be used as liquid smoke to control Ipomea batatas . At a temperature of between 300 - 450 Â°C, liquid smoke is produced through a pyrolysis process. Pyrolysis produces phenolic chemicals and aldehydes that have antioxidant and antimicrobial properties (anti-bacterial and anti-fungal). The assessment of pH, acidity, and phenol concentration characterizes the quality of liquid smoke. The potential of red fruit seed waste as a liquid smoke product for biopesticides in Ipomea batatas is explored in this study. Additionally, study development aims to determine the optimal method for pyrolyzing red fruit seed waste, its characteristics, chemical content, and the way to use liquid smoke as a biopesticide in Ipomea batatas . The results showed that the liquid smoke of grade 3 red fruit seed waste contains 7 components that can be detected using a mass spectrometer. The higher the concentration of liquid smoke produced by grade 3 red fruit seeds, the higher the possibility of Cylas formicarius mortality. Cylas formicarius had the highest mortality rate (90%) when tested at a 7% test solution concentration.